Model Identification and Control for a Quarter Car Test Rig of Series Active Variable Geometry Suspension - Yu,M; Evangelou,SA; Dini,D (Elsevier, 2017)
In this paper, a quarter car test rig is utilized to perform an experimental study of the singlelinkvariant of the Series Active Variable Geometry Suspension (SAVGS). A nonlinear model of the testrig is identified with the use of a theoretical quarter car model and the rig’s experimental frequencyresponse. A linear equivalent modeling method that compensates the geometric nonlinearity is alsoadopted to synthesize an H-infinity control scheme. The controller actively adjusts the single-linkvelocity in the SAVGS to improve the suspension performance. Experiments are performed to evaluatethe SAVGS practical feasibility, the performance improvement, the accuracy of the nonlinear model andthe controller’s robustness.